Liver Proteome Profile of Growth Restricted and Appropriately Grown Newborn Wistar Rats Associated With Maternal Undernutrition - Sarli, Polyxeni-Maria; Manousopoulou, Antigoni; Efthymiou, Elias; Zouridis, Andreas; Potiris, Anastasios; Pervanidou, Panagiota; Panoulis, Konstantinos; Vlahos, Nikolaos; Deligeoroglou, Efthymios; Garbis, Spiros D.; Eleftheriades, Makarios (Frontiers in Endocrinology, 2021)
Background: Fetal Growth Restriction (FGR) has been associated with adverse perinatal outcomes and epigenetic modifications that impact gene expression leading to permanent changes of fetal metabolic pathways and thereby influence development of disease in childhood and adult life. In this study, we investigated the result of maternal food restriction on liver protein expression in Wistar male newborn pups. Materials & methods: Ten (n=10) timed pregnant Wistar rats on their 14th day of gestation were randomly assigned to either control (n=4) or food restricted group (n=6). The control group had ad libitum access to food. In the food restricted group, maternal diet was limited in a moderate fashion (50%) from day 15 of pregnancy until delivery. All rats delivered spontaneously on day 21 and newborn pups were immediately weighed. Pups born to normally nourished mothers were considered as controls, while pups born to food restricted mothers were subdivided into two groups, based on their birth weight: growth restricted (FGR) and appropriately grown (non-FGR). Rats were euthanized immediately after birth and liver tissues of 11 randomly selected male offspring (FGR n=4, non-FGR n=4, control n=3) were collected and analyzed using quantitative proteomics. Results: In total 6665 proteins were profiled. Of these, 451 and 751 were differentially expressed in FGR and non-FGR vs. control respectively, whereas 229 proteins were commonly expressed. Bioinformatics analysis of the differentially expressed proteins (DEPs) in FGR vs. control revealed induction of the super-pathway of cholesterol biosynthesis and inhibition of thyroid hormone metabolism, fatty acid beta oxidation and apelin liver signaling pathway. Analysis of DEPs in non-FGR vs. control groups showed inhibition of thyroid hormone metabolism, fatty acid beta oxidation and apelin liver signaling pathway. Conclusion: This study demonstrates the impact of prenatal food restriction on the proteomic liver profile of FGR and non-FGR offspring underlying the importance of both prenatal adversities and birth weight on liver dependent postnatal disease.